Pemberdayaan Ekonomi Mikro dalam Pembuatan Kreasi Piring dengan Media Lidi Sawit - Nur Alfi Khatamin; Wiwik Damayanti; Tohir Muntoha; Nur Azizeh (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2022)
In our environment there are a lot of things that we think of as leftovers, but in the hands of experts, things that are considered useless can be turned into valuables and have high artistic value, this service uses palm sticks to become woven plates, fruit bowl and parcel. Tiyuh Panaragan is an oil palm plantation area that has plantation waste in the form of multiple palm sticks which have only been destroyed by burning. The purpose of this service is to improve the entrepreneurial skills of the community by utilizing palm sticks and shaping them into objects that are beautiful and useful and have a high selling value. The method used in this mentoring is Asset Based Community Development (ABCD). This assistance utilizes the potential of the Tiyuh Panaragan community in Tulang Bawang Tengah District, Tulang Bawang Barat Regency. The result of this service is the mastery of the skills provided in this activity so that the ability of these excellent skills can benefit in increasing entrepreneurship and in the end it can improve the community's economy. Thus the community service in increasing entrepreneurship with the creation of this oil palm stick is running smoothly, although there are several obstacles, these obstacles can be overcome. The skills given in this activity provide more knowledge and skills by utilizing palm oil waste which has been used as waste which has not been utilized properly.